IDENTIFIKSI FAKTOR PETERNAK DAN PEMILIK MODAL MELAKUKAN SISTEM BAGI HASIL TESENGSAPI POTONG DI DESA BATU PUTE, KECAMATAN SOPPENG RIAJA, KABUPATEN BARRU - Zainabriani, sitti Nurani Sirajuddin; Ikrar Mohammad Saleh (Jurnal Ilmu dan Industri Peternakan, 2015)
ABSTRACT. This study aimed to find out the reason - alasan peternak and financiers did sharecropping system (teseng) beef cattle business pute Stone Village, District Soppeng Riaja, Barru, This t ype of research using data adalaheksploratif quantitative and qualitative, which began in October 2014 - February 2015 pute Stone Village, District Soppeng Riaja, Barru. Data collected through interviews with the help of a questionnaire. Analysis of the data used is descriptive statistics by using metodeDelbecq. The main factor breeder (Pa ‘Tesseng) perform system for the results are: lack of capital, want to have your own farm, economic demands, request family, additional revenue, the main factors of capital owners (Ma’Teseng) melakukam system for the results are: lack of time in maintenance, want to help, want to earn a profit, lack of land, the number of cattle was too much.